Interactions between Financial Leverage and Product Quality in the Tourism & Leisure Industry: Testing the Moderating Role of Business Conditions - Sodeyfi, Setareh (Eastern Mediterranean University EMU - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
The present study develops a new model and proposes new research impetus by searching the effects of financial leverage and its related control variables on the level of product quality offered by business firms. Another contribution of this research study to the literature is that the moderating role of business conditions in the effects of financial leverage on product quality is tested. Due to its importance among the other sectors, tourism and leisure industries have been selected in the case of United Kingdom (UK). The selection of the UK is important since it ranks 8th in attracting international tourists as of 2015 according to the statistics of World Tourism Organization. A panel data of 80 tourism and leisure firms in the UK have been constructed on quarterly basis as they were available from Thomson Reuters’ DataStream. Results of empirical analyses provide a strong evidence of negative effects of financial leverage on product quality. Financial leverage impact negatively on firm-level investments as well. This study finds that business conditions and macroeconomic performance in the UK have positively significant effects on firmlevel product quality; this shows that any positive climate in business environment at macro level would contribute to promotion of the quality levels of products offered by business firms. Another major finding of this new research study is that business conditions at macro level have significant moderating role in the relationship between financial leverage and product quality. This reveals that leverage positions of business firms are closely linked to business environment and this reality significantly impact on the level of product quality. This research study provides important and significant policy implications for policy makers. Keywords: Leverage; Investment; Product Quality; Tourism; Leisure; Moderating Role.

ÖZ: Bu çalısma sahada ilk kez yeni bir model ve arastırma konusu önermektedir. Söyle ki, ilk kez finansal kaldıraç aracının ve baglantılı oldugu diger faktörlerin isletmelerin sunmus oldugu ürünlerin kalite seviyesine olan etkisi incelenmistir. Bu çalısmanın, sahaya diger bir etkisi ise, yine ilk kez, makro seviyede is hayatı kosullarının ve makroenomik gelismelerin finansal kaldıraç ile ürün kalite seviyesi arasındaki iliskiye anlamlı bir etki edip etmedigi de incelenmistir. Bu baglamda, diger sektörler arasında çok önemli bir yere sahip olan turizm ve konaklama (sehayat, tatil) sektörü seçilmisdir. Ülke olarak, Dünya Turizm Örgütü raporuna göre 2015 yılı itibariyle dünya turizm sıralamasında 8. sırada olan ngiltere seçilmistir. Çalısmayı yürütebilmek için ngiltere’de faaliyet gösteren ve Thomson Reuters kaynaklı DataStream veritabanında mevcut 80 firma seçilip panel verileri olusturulmustur. Sonuçlar, finansal kaldıraç oranlarının güçlü bir sekilde firma yatırımları ve ürün kalitesi üzerinde negatif yönde etki ettigini göstermektedir. Diger taraftan, ülkedeki is kosulları ve makroekonomik performans da finansal kaldıraç aracılıgı ile ürün kalitesine etki etmektedir. Bu çalısmanın diger bir temel bulgusu da, is kosullarının ve makroekonomik performansın finansal kaldıraç ile ürün kalitesi arasındaki iliskiye de yüksek oranda anlamlı etki ettigi ortaya çıkarılmıstır. Sahada ilk kez yapılan böyle bir çalısmanın bulguları, firmaların yönetimleri açısından çok önemli mesajlar içermekte olup metin içerisinde tartısılmıstır. Anahtar Kelimeler: Kaldıraç; Yatırım; Ürün Kalitesi; Turizm; Dinlenme; Aracı Rol.
Doctor of Philosophy in Banking and Finance. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2017. Co-Supervisor: Prof. Dr. Salih Katırcıoğlu, Supervisor: Prof. Dr. Hasan Kılıç
Keywords: Banking and Finance; Financial Leverage-Tourism and Leisure Industry; Leverage; Investment; Product Quality; Tourism; Leisure; Moderating Role